CONDUCTIVITY AND ELECTROHYDRODYNAMIC FLOWS IN LIQUID DIELECTRICS - OSTAPENKO, Anatoly; ZHURAVLYOV, Mikhail (My University, 2018)
Study the possibility of developing the technical and technological utilization the liquid dielectrics (hydrocarbon and hydro silicous liquids).
Keywords: EHD flow; ion-molecular structures; high voltage; liquid dielectrics